2014
DOI: 10.1080/09593330.2014.941944
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different pH-values on process parameters in two-phase anaerobic digestion of high-solid substrates

Abstract: In many publications, primary fermentation is described as a limiting step in the anaerobic digestion of fibre-rich biomass [Eastman JA, Ferguson JF. Solubilization of particulacte carbon during the anaerobic digeston. J WPCF. 1981;53:352-366; Noike T, Endo G, Chang J, Yaguchi J, Matsumoto J. Characteristics of carbohydrate degradation and the rate-limiting step in anaerobic digestion. Biotechnol Bioeng. 1985;27:1482-1489; Arntz HJ, Stoppok E, Buchholz K. Anaerobic hydroysis of beet pulp-discontiniuous experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 36 publications
1
16
0
2
Order By: Relevance
“…Deublein and Steinhauser [35] showed that pH > 10 caused an irreversible loss of the activity of the microorganisms. The pH values between 5.5 and 6.5 were often reported as an optimal range and the best pH values was 6.0 [54,[82][83][84]. These results are reasonable for each condition of hydrolysis and acidogenesis as presented in section 2.1.…”
Section: The Hydrolytic/acidogenic Reactorsupporting
confidence: 73%
“…Deublein and Steinhauser [35] showed that pH > 10 caused an irreversible loss of the activity of the microorganisms. The pH values between 5.5 and 6.5 were often reported as an optimal range and the best pH values was 6.0 [54,[82][83][84]. These results are reasonable for each condition of hydrolysis and acidogenesis as presented in section 2.1.…”
Section: The Hydrolytic/acidogenic Reactorsupporting
confidence: 73%
“…Furthermore, it must also be taken into account that, in an agricultural biogas digester fed with renewable biomass, along with proper supplementation of macro-and micronutrients (trace metals), optimization of process variables, such as pretreatment techniques applied to the biomass, temperature, pH and mixture ratios (if the biogas plant is operated in co-digestion mode), is also of paramount importance. [35][36][37][38][39] …”
Section: Methane Yields Obtained From Maize Silage By Ni Co and Mo Smentioning
confidence: 98%
“…This condition corresponds to HR effluent and MR influent with pH adjusted to 7 with the purpose of emulate the neutral conditions of the methanogenic stage of the two-stage AD process. pH values in a range of 7.0-7.5 favor the methanogenic stage of the anaerobic digestion process since this factor increases biogas production and the specific CH 4 yield [28]. Under these conditions, the bed expanded faster than in tests with the S1 substrate.…”
Section: Colonized Extendosphere ® Expansionmentioning
confidence: 99%